2009
DOI: 10.1152/japplphysiol.91365.2008
|View full text |Cite
|
Sign up to set email alerts
|

Signals of motor command bias joint position sense in the presence of feedback from proprioceptors

Abstract: Joint position sense is believed to be mediated by muscle afferent signals. Because a "phantom" hand produced by a sensory and motor nerve block appears to move in the direction of voluntary effort, signals of "motor command" or "effort" can influence perceived joint position. To determine whether this occurs when sensory signals are available, three studies assessed position sense when motor command and afferent signals were available, but joint movement was prevented. First, the hand was positioned to stop m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 46 publications
6
82
0
2
Order By: Relevance
“…As Smith et al [22] reported, these signals of motor command can bias joint position sense in the presence of feedback from proprioceptors.…”
Section: Discussionmentioning
confidence: 96%
“…As Smith et al [22] reported, these signals of motor command can bias joint position sense in the presence of feedback from proprioceptors.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, other works have insisted on the role of the central command necessary to overcome gravitational load in limb position sense (Gandevia et al 2006;Smith et al 2009;Walsh et al 2009). In the framework of the present experiment, however, it proves difficult to favor one hypothesis over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Motor commands or motor intention (also known as ''efference copies'') are for example known to interact with afferent signals to generate sensation, and are known to contribute to joint position sense (Smith et al, 2009). Under normal circumstances there is an integration of intention, action and sensory feedback.…”
Section: Altered Sensorimotor Processing Following Spinal Manipulationmentioning
confidence: 99%